2018
DOI: 10.1101/285338
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immuno-genomic PanCancer Landscape Reveals Diverse Immune Escape Mechanisms and Immuno-Editing Histories

Abstract: Immune reactions in the tumor micro-environment are one of the cancer hallmarks and emerging immune therapies have been proven effective in many types of cancer. To investigate cancer genomeimmune interactions and the role of immuno-editing or immune escape mechanisms in cancer development, we analyzed 2,834 whole genomes and RNA-seq datasets across 31 distinct tumor types from the Pan-Cancer Analysis of Whole Genomes (PCAWG) project with respect to key immunogenomic aspects. We show that selective copy number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…This figure demonstrates the high sensitivity of ALPHLARD-NT (88 mutations) compared with POLYSOLVER (60 mutations) and EBCall (80 mutations), which is especially remarkable for insertions. ALPHLARD-NT detected seven insertions at the beginning of exon 4 of HLA class I genes, which is a known hotspot of indels (Mizuno et al, 2018), whereas POLYSOLVER and EBCall identified no and three insertions at this hotspot, respectively. ALPHLARD-NT also identified 12 deletions at the same position.…”
Section: Resultsmentioning
confidence: 99%
“…This figure demonstrates the high sensitivity of ALPHLARD-NT (88 mutations) compared with POLYSOLVER (60 mutations) and EBCall (80 mutations), which is especially remarkable for insertions. ALPHLARD-NT detected seven insertions at the beginning of exon 4 of HLA class I genes, which is a known hotspot of indels (Mizuno et al, 2018), whereas POLYSOLVER and EBCall identified no and three insertions at this hotspot, respectively. ALPHLARD-NT also identified 12 deletions at the same position.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, substantial evidence indicates that tumor-specific peptides that result from such variations can bind to a major histocompatibility complex (MHC) molecule and be presented to antitumor T cells on the surface of a tumor cell. Identification of such tumor-specific peptides, termed neoantigens, has been receiving increasing attention because of its numerous potential applications in cancer immunotherapy ( Carreno et al , 2015 ; Matsushita et al , 2012 ; Mizuno et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…It can automatically construct mutant peptides from vcf files or mutant RNA sequences and calculate their binding capability to the corresponding HLAs with some information for filtering. This tool has been used in the Mitochondrial Genome and Immunogenomics Working Group in the PanCancer Analysis of Whole Genomes (PCAWG) project ( Mizuno et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent technological advances in massively parallel sequencing have enabled 2 identification of genetic variants, e.g., single nucleotide variants (SNVs) and insertions 3 or deletions (Indels), in individual cancer patients. Furthermore, substantial evidence 4 indicates that tumor-specific peptides that result from such variations can bind to a 5 major histocompatibility complex (MHC) molecule and be presented to antitumor 6 T-cells on the surface of a tumor cell. Identification of such tumor-specific peptides, 7 termed neoantigens, has been receiving increasing attention because of its numerous 8 potential applications in cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond 69 previously developed platforms, it can cover specific cases and include additional 70 information for filtering. The package, documentation, and sample analysis are 71 available at http://github/hase62/Neoantimon, and an analysis result in PCAWG 72 project is also available[5]. An overview of the input and output file information of the package.…”
mentioning
confidence: 99%